2015
DOI: 10.3233/nre-151225
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive remediation of attention deficits following acquired brain injury: A systematic review and meta-analysis

Abstract: Cognitive rehabilitation resulted in short-term improvements in divided attention following stroke, but not after TBI or CNS-impacting malignancy. Cognitive interventions did not significantly improve other attentional domains in participants with stroke, TBI or CNS-impacting malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…The mean effect estimates for CT and CS across the different populations suggest modest efficacy. For stroke, we found that meta-analyses of CT interventions targeting a specific cognitive domain, such as memory (das Nair et al, 2016) and attention (Loetscher & Lincoln, 2013;Virk et al, 2015) showed no significant effect, however, results were imprecise and based on a small number of primary trials. In contrast, there was evidence from a moderate-quality review including 22 primary trials covering a variety of cognitive remediation techniques (Rogers et al, 2018), to support the use of COTs to improve cognitive performance following stroke.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean effect estimates for CT and CS across the different populations suggest modest efficacy. For stroke, we found that meta-analyses of CT interventions targeting a specific cognitive domain, such as memory (das Nair et al, 2016) and attention (Loetscher & Lincoln, 2013;Virk et al, 2015) showed no significant effect, however, results were imprecise and based on a small number of primary trials. In contrast, there was evidence from a moderate-quality review including 22 primary trials covering a variety of cognitive remediation techniques (Rogers et al, 2018), to support the use of COTs to improve cognitive performance following stroke.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…Three reviews reported meta-analytical results for CT for stroke (das Nair et al, 2016;Loetscher & Lincoln, 2013;Virk et al, 2015). The mean effect estimate was 0.23 (-0.19 to 0.65).…”
Section: Cognitive Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 These differing perspectives continue to co-exist in the literature. [7][8][9][10] Unfortunately, there is a dearth of empirical evidence to guide a clinician's decision-making as to when to provide challenging interventions, compensatory activities, and metacognitive strategies in TBI inpatient rehabilitation. The evidence that does exist is based on applications in alternative settings and with different levels of acuity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%